Supersymmetric five-point gluon amplitudes in AdS space - Alday, LF; Gonçalves, V; Zhou, X (American Physical Society, 2022)
We present the tree-level five-point amplitude of the lowest Kaluza-Klein mode of super-Yang-Mills theory on AdS5 × S3, dual to the correlator of the flavor current multiplet in the dual 4d N = 2 superconformal field theory. Its color and kinematical structure is particularly simple and resembles that of the flat-space gluon amplitude.